FORMATION OF ANTIFRICTION SURFACE STRUCTURES UNDER FRICTION - Shchepetov, Vitalii; Kharchenko, Olena; Kharchenko, Serhii; Kalinichenko, Vitalii (Problems of Friction and Wear, 2023)
The results of the formation of anti-friction surface structures of the developed glass-composite self-lubricating nanocoatings, the structural components of which have a qualitative effect on the graphitization process and ensure the production of a surface layer of α-graphite that minimizes contact parameters, are presented. The positive role of the glass phase in the form of aluminoborosilicate, which affects the tribotechnical properties of coatings, has been established. It is noted that the increase in adhesive strength is achieved due to the formation of a surface layer of vitreous sodium silicate during sputtering. It was established that the intercalation of the graphite layer with particles of the subsurface zone does not significantly affect the tribotechnical characteristics. The developed nanostructured glass composite coatings showed high anti-friction characteristics in the entire load-speed range of tests.